Whole-body predictors of wrist shot accuracy in ice hockey: A kinematic analysis by way of motion capture - Magee, P. (Department of Kinesiology and Physical Education, McGill University, 2009)
The purpose of this study was to identify joint angular kinematics that correspond to shooting accuracy in the stationary ice hockey wrist shot. Twenty-four subjects participated in this study, each performing 10 successful shots to four shooting targets. An eight-camera infra-red motion capture system (240 Hz), using passive reflective markers, was used to record motion of the joints, hockey stick, and puck throughout the performance of the wrist shot. A multiple regression analysis was carried out to examine whole-body kinematic variables with accuracy scores as the dependent variable. Results indicate that no one body region predominated as a predictor of accuracy across all four shooting targets since the wrist shot's general movement pattern required that one or more of the body's joints modulate its movement amplitude, rate and timing to achieve an accurate outcome. Significant accuracy predictors were identified in the lower limbs, torso and upper limbs. An accurate outcome was associated with the following characteristics: The lower body seemed to provide a stable base for support, but also contributed to initiation of movement in the form of weight transfer towards the intended target. We propose that the trail leg seemed to offset rotational motion that could potentially upset the stability of the system if not properly managed. Additionally, angular kinematics at the pelvis, spine and thorax appeared to orient the trunk such that the upper limbs can optimally function to achieve an accurate outcome, and also undoubtedly contributed to force production. And finally, accuracy was associated with more dynamic use of the lead arm specifically at the wrist and shoulder.